Distribution Grid Fault Location Applying Transient Zero-mode Current - Hongsheng Su; Yunchuan Zhang (Institute of Advanced Engineering and Science, 2012)
To aim at the puzzles on faults location in distribution grids, the paper analyzed the distributing characteristics of transient zero-mode currents as the faults occurred, with the aid of correlation theory, a new fault circuit-selection and fault-location method was proposed based on transient zero model current for power distribution grid faults. The method is based on such a fact that the RMS was maximum of fault line transient zero-mode current, and the inner products between it and other line transient zero-mode current were less than zero, in addition, the transient zero-model currents at two sides of the fault point possessed opposite polarity and diverse waveform, and as well as small correlation coefficient closer to zero. In the end, the simulation results show that the proposed method on circuit-selection and fault-location for power distribution grids fault based on transient zero- mode current is correct and effective, and not affected by voltage epoch angle, and grounding resistance, and as well as neutral-point grounding modes. DOI: http://dx.doi.org/10.11591/telkomnika.v10i5.1289